The effect of light on the early growth wheat (Triticum aestivum L) - Novia Destiana; Einstivina Nuryandani; Sri Kurniati Handayani; Diki Diki (Program Studi Pendidikan Biologi, Pascasarjana, Universitas Pattimura, 2022)
Triticum aestivum L is a cereal plant that grows optimally in a subtropical climate. In tropical climate wheat growth experieces various obstacles such as high air temperature and humidity, and intensity of light. Study of wheat conditions for the growth of this plant in tropical areas such as Indonesia is needed. This study aims to determine the effect of light on the germination, growth, and early development of wheat.this is an experimental research with two treatments, the first group was in normal light and the the second was without light. Each treatment was carried out using 30 replications. The analysis was carried out by comparing the average value of plant length and plant morphology from eight days of observation on two kinds of treatments. The results showed that there were differences in plant height in the two treatments. The average plant height on the 8th day in normal light treatment was 9.76 cm, while the average plant height with the treatment without light was 10.1 cm. Observations of growth on the morphology of wheat plants showed that plants with no light treatment experienced a slowdown in the opening of the second leaf, had a paler color and thinner leaf blades, compared to plants grown with light treatment. The absence of light accelerates the germination process and increases the height of wheat plants, but at a later stage it can slow down the development of these plants.